Technological imperatives for issues in certification of quality, progress, and payments in construction projects: A systematic review - G. Thilini Weerasuriya; Srinath Perera; Rodrigo N. Calheiros (Construction Economics and Building)
Construction projects require certification of quality and progress of work and related payments to ensure successful completion. However, several issues related to quality, progress and payment certifications exist in the construction industry. A two-stage systematic review of literature was conducted to understand issues and appropriate solutions related to quality, progress, and payment certifications in construction projects. The literature review, following PRISMA guidelines, retrieved journal articles in Scopus and Web of Science, published between 2008 and 2023. In stage one, 1450 records were retrieved through search queries on prevalent issues and 50 articles were selected after applying inclusion criteria and screening. Stage two of the review sought technological imperatives that mapped to the pinpointed issues. 1262 search results were screened using the same criteria as the first stage, producing 45 articles. The studies related to quality and progress certification highlighted issues such as defects, failures, and rework, delayed project completion, and inaccurate documentation and reporting. Payment certification related articles discussed issues like payment delays and non-payments, payment disputes, and insolvency. Building Information Modelling, artificial intelligence, and blockchain technology and smart contracts were highlighted as the major technological imperatives for solving these issues. These technologies support rigorous inspections, ensure compliance of building materials and products, enable contract fulfilment, and guarantee payments, thereby effectively addressing the issues. The study strongly advocates for blockchain and smart contracts as a comprehensive technological solution to overcome certification-related challenges in construction projects.